The Influence of Risk Perception and Trust on Investment Decisions - Rieneke Ryke Kalalo; Ristati; Chairil Akhyar; Nurlela; Sean Michael Owen Wijaya (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of risk perception and trust on investment decisions in Indonesia. This study used a quantitative approach, collecting data through questionnaires from respondents with investment experience. The sampling technique used purposive sampling, while data analysis was conducted using multiple linear regression. The results indicate that risk perception and trust influence investment decisions. Risk perception makes investors more cautious in making investment choices, while trust in investment institutions or platforms can increase investor confidence in investing. Thus, risk perception and trust are important factors in influencing people's investment decisions.